利用自噬作用消除转移性黑色素瘤中的丝裂原活化蛋白激酶抑制剂诱导的耐药性. (4th February 2019) - Verykiou, S.; Alexander, M.; Edwards, N.; Plummer, R.; Chaudhry, B.; Lovat, P.E.; Hill, D.S.
Abstract : Linked Article: Verykiou et al. Br J Dermatol 2019;180 :346–356